Intermediation in peer-to-peer markets: Evidence from auctions for personal loans - Thilo Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
I examine the role of intermediaries on the world's largest peer-to-peer online lending platform. This marketplace as well as other recently opened lending websites allow people to auction microcredit over the internet and are in line with the disintermediation in financial transactions through the power of enabling technologies. On the online market, the screening of potential borrowers and the monitoring of loan repayment can be delegated to designated group leaders. I find that, despite superior private information, these financial intermediaries perform worse than the average lender with respect to borrower selection. I attribute this to deliberately sending wrong signals. Bivariate probit estimates of the effect of group membership on loan default indicate positive self selection into group loans. That is borrowers with worse observed and unobserved characteristics select into this contract form. I provide evidence that this is due to a missleading group reputation system that is driven by a short term incentive design, which was introduced by the platform to expand the market and has been discontinued. I further find that, after controlling for this group growth driven selection effect, group affliation per se significantly reduces the probability of loan default.
Keywords: C57; D02; D47; D82; G21; O16; 330; peer-to-peer; finance; market design; matching; auctions